1949
DOI: 10.1071/bi9490438
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sympathectomy on Wool Growth

Abstract: SummaryFive sheep (two Merinos, two Corriedales, and one crossbred) were subjected to unilateral thoracic sympathectomy. Fleece samples were collected at 28-day intervals, for a period of seven months, from tattooed areas of skin on both the sympathectomized and control sides.The results show a mean increase of 36 per cent. in wool growth rate on the sympathectomized side over the control side for ten weeks after the operation. This effect then disappeared so that no difference between the two sides was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

1953
1953
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
3
9
1
Order By: Relevance
“…The differences in the weight of the haircoat are less easily explained on the basis of the above hypothesis. In sheep, Ferguson (1949) has shown that if the animal is unilaterally sympathectomized, wool growth is enhanced on the side where the nerves have been cut. From this fact it might be expected that the pigs in the warm climate with the better blood supply would have the greater quantity of hair.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the weight of the haircoat are less easily explained on the basis of the above hypothesis. In sheep, Ferguson (1949) has shown that if the animal is unilaterally sympathectomized, wool growth is enhanced on the side where the nerves have been cut. From this fact it might be expected that the pigs in the warm climate with the better blood supply would have the greater quantity of hair.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the increased wool production per follicle was partly due to the greater availability of nutrients following the destruction of many of the cutaneous nerves. Ferguson (1949) obtained a mean increase of 36 % in wool growth rate for 10 weeks following unilateral sympathectomy and suggested that it was due to vasodilation of the denervated vessels. Slen (1958) suggested that mechanical trauma (such as that caused when a sheep is bumped), with its concomitant increase in blood supply to the site of injury, stimulated the growth of wool.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the faster length growth rate, or increased length of the hair growth cycle, was partly due to the availability of more nutrients following the destruction of the sweat glands and many of the cutaneous nerves. Ferguson (1949) reported an increase of 36% in wool growth rate following sympathectomy and suggested that it was brought about by vasodilation of the denervated blood vessels. Further studies are needed in order to determine the influence of the various skin structures on the growth of hair or wool.…”
Section: Discussionmentioning
confidence: 99%